Assessing Groundwater Quality in Rural Communities: A Detailed Study of Physical, Chemical, and Microbial Contaminant - Herawati, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The reliance of rural communities on groundwater as the primary source of clean water presents significant challenges, particularly due to limited access to water treatment systems. This study aims to fill the knowledge gap regarding groundwater quality in rural areas of Indonesia, focusing on physical, chemical, and microbiological parameters. Using a descriptive quantitative method, 15 groundwater samples were analyzed to assess their quality. The findings revealed that most samples had physical and chemical qualities that were still within safe limits. However, a noteworthy discovery was the high levels of Coliform bacteria contamination in some samples, indicating serious health risks for the community. Additionally, nitrate levels approaching the WHO maximum limit were detected, suggesting potential impacts of agricultural activities on water quality. Although groundwater quality is generally considered good, these results highlight the importance of improving water and sanitation management to prevent greater health risks. This research provides essential insights for policy-making and underscores the urgent need for better water treatment infrastructure in rural areas.